(untitled) (Palíndromo, 2014)
The topic presented in this article is the reading of images in electronic games. The article contains the data of a research developed for the Education Post Graduate Program at Universidade Federal de Santa Catarina, whose subjects are students that are finishing Middle School at Colégio de Aplicação, at UFSC. The main theoretical framework is an image reading approach developed by Sandra Regina Ramalho e Oliveira, from the perspective of Discursive Semiotics.